PENGARUH TINGKAT KECUKUPAN MODAL, RASIO PINJAMAN BERMASALAH DAN RASIO PINJAMAN DANA PIHAK KETIGA TERHADAP PROFITABILITAS - Khodijah, Siti (COMPETITIVE, 2021)
Before investing, an investor must analyze the company's financial performance. Therefore, investors must know what factors affect profitability. For this reason, this research intends to see whether there is an impact between the level of capital adequacy, non-performing loans and the use of third party funds on the profitability of the sample companies. Purposive Sampling method is used in determining samples with certain criteria in order to obtain 5 samples. This study obtained data sources from the Annual Reports of each sample bank. Profitability is negatively affected by NPL and not influenced by CAR and LDR, this result is shown from the Partial Test (t test). CAR, NPL, and LDR have a simultaneous effect on profitability, this is indicated by the simultaneous test (f test).